The Impact of Discovery Learning Model Based on High Order Thinking Skills (HOTS) in Learning Arabic on Students Analytical Thinking Skills - Ayu Desrani; Zakiyah Arifa; Susanto Susanto (Taqdir, 2021)
This research aimed to examine the impact of discovery learning model based on higher-order thinking skills (HOTS) on students' analytical thinking skills in learning Arabic. The research was a quantitative approach and experiment method (quasi-experiment research), using post-test control and experiment group design. The population in this research was the students of class X Islamic Senior High School (MAN) 1 Malang East Java, Indonesia. The sampling was taken using the cluster random sampling technique. The instrument used to collect data was a test balance. It was analyzed using SPPS with the independent sample t-test formula. The results of this research are: the significance value of variable analysis is 0.00 <0.05. It means there is an impact of the discovery learning model based on higher-order thinking skills (HOTS) on students' analytical skills. Implicitly, it can improve students' abilities in understanding the material, therefore the students can think analytically when they find problems in learning.